Molecular profiling of follicular fluid microRNAs in young women affected by Hodgkin lymphoma. Issue 6 (December 2021) - Caponnetto, Angela; Battaglia, Rosalia; Ragusa, Marco; Barbagallo, Davide; Lunelio, Federica; Borzì, Placido; Scollo, Paolo; Purrello, Michele; Vento, Maria Elena; Di Pietro, Cinzia
Abstract: Research question: Treatments for Hodgkin lymphoma have improved but one of their common effects is gonadal toxicity, which contributes to fertility damage of patients and induces temporary or irreversible loss of fertility. Could micro-RNA (miRNA) expression profiles in follicular fluid be influenced by Hodgkin lymphoma? Could their alteration affect molecular pathways involved in follicle growth and oocyte maturation? Design: miRNA expression profile was investigated in follicular fluid samples from young women affected by Hodgkin lymphoma compared with healthy controls by NanoString technology. Bioinformatic analysis was used to verify miRNA involvement in follicle development and miRNA deregulation with Hodgkin lymphoma in a larger cohort of follicular fluid samples was confirmed by real-time quantitative polymerase chain reaction. Results: Thirteen miRNAs are deregulated in Hodgkin lymphoma samples compared with controls and are involved in molecular pathways related to cancer, gametogenesis and embryogenesis. Among them, let-7b-5p, miR-423-5p, miR-503-5p, miR-574-5p and miR-1303 are implicated in biological processes related to follicle development and oocyte maturation. Let-7b-5p holds the central position in the regulatory network of miRNA–mRNA interactions, has the highest number of mRNA target genes shared with the other differentially expressed miRNAs and is significantly downregulated in Hodgkin lymphoma follicular fluid samples. Conclusions: These data led us to question the potential influence of miRNA deregulation on oocyte quality. Further studies are needed to verify the reproductive potential of young patients with Hodgkin lymphoma before starting chemotherapy protocols and an adequate protocol of fertility preservation needs to be guaranteed.